Evangelical commentary on the Bible - Elwell, Walter A.; Baker Bytes (Firm) (Grand Rapids, MI : Baker Book House, 1995)
Searchable commentary based on the New International version of the Bible. Includes outlines, introduction to every book of the Bible, discussions of key doctrines, and print, bookmark, and notebook functions.
Title from disk label.
Edited by Walter A. Elwell.
System requirements: 386 PC; 4MB RAM; Windows 3.1 or Windows 95; CD-ROM drive.
Keywords: Bible -- Commentaries; Bible -- Study and teaching